Coating process method for high-refractive-index and wear-resistant glass beads
By cleaning, surface active catalysis and dynamic coating treatment of glass microbeads, combined with specific coating and microwave curing, the contradiction between the high refractive index and wear resistance of glass microbeads in asphalt pavement is solved, the high refractive index and wear resistance are improved, and the service life is extended.
Patent Information
- Application Number
- CN202510716797.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-05-30
- Publication Date
- 2025-10-17
AI Technical Summary
When existing glass microbeads are used in asphalt pavements, there is a contradiction between high refractive index and wear resistance, resulting in poor reflection suppression effect and short service life.
After cleaning and removing impurities from the glass beads and subjecting them to surface active catalytic treatment, they are immersed in a coating solution of specific components for dynamic coating. A composite coating of perfluorooctyltriethoxysilane and hydroxy acrylic resin is sprayed on them, and combined with microwave curing treatment, a high-refractive-index, wear-resistant coating is formed.
The refractive index and wear resistance of glass beads are improved, the service life on asphalt pavement is extended, and better reflection suppression effect is provided.
Smart Images

Figure CN120794404A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The application relates to the technical field of glass microbeads, in particular to a coating process method of high-refractive and wear-resistant glass microbeads. BACKGROUND
[0002] In the field of road engineering, the light reflection problem of asphalt pavement has long plagued traffic safety. Although the traditional glass microbeads can improve the night visibility, the difference between the refractive index of the glass microbeads and the asphalt base material is insufficient, so that the light reflectivity is as high as 15% to 20%, which easily causes the glare of the driver. In order to solve the problem, the prior art adopts the ways of coating aluminum on the glass microbeads and adding high-purity TiO2 coating layer. However, the former has the defects of poor wear resistance and rapid reflectivity attenuation, and the latter has the defect of easy abrasion. Moreover, the conventional way of adding the TiO2 coating layer is to directly add the nano TiO2. Since the surface energy of the nano TiO2 is high, the nano TiO2 is easy to agglomerate into micrometer particles, so that the refractive index of the coating layer is uneven, thereby causing the light reflection inhibition effect to decrease. In addition, the physical mixed nano TiO2 has poor adhesion with the base material and insufficient wear resistance.
[0003] Based on the search of the above-mentioned data, it can be seen that there is a contradiction between the high refractive index and the wear resistance of the existing glass microbeads when they are applied in the asphalt pavement. Therefore, the application provides a coating process method of high-refractive and wear-resistant glass microbeads. SUMMARY
[0004] In view of the defects of the prior art, the application provides a coating process method of high-refractive and wear-resistant glass microbeads, which solves the problem of the contradiction between the high refractive index and the wear resistance of the existing glass microbeads when they are applied in the asphalt pavement.
[0005] To achieve the above object, the application is implemented by the following technical scheme: a coating process method of high-refractive and wear-resistant glass microbeads, specifically comprising the following steps:
[0006] S1, after the glass microbeads are cleaned and impurities are removed, the glass microbeads are subjected to surface active catalysis treatment;
[0007] S2, the glass microbeads are immersed in a coating liquid for dynamic coating;
[0008] S3, a full-fluorooctyl triethoxysilane and a hydroxy acrylate resin composite coating layer are sprayed on the glass microbeads, the glass microbeads are naturally dried, then immersed in a 1wt% gamma-aminopropyl triethoxysilane ethanol solution for 10 to 15 minutes, subjected to post-treatment, and then subjected to microwave curing treatment, so as to obtain high-refractive and wear-resistant glass microbeads.
[0009] The application is further provided as follows: the way of cleaning and removing impurities from the glass microbeads in S1 comprises:
[0010] The waste glass is put into an electric melting furnace to be remelted to prepare the glass microbeads with a granularity of 60-120.
[0011] The glass beads are immersed in 5wt% hydrofluoric acid and ultrasonically cleaned for 15 min;
[0012] The glass beads are taken out and sprayed with deionized water for 3 min;
[0013] The impurities are removed by drying with ethanol vapor for 10 min.
[0014] The application further provides that the surface catalytic treatment of the glass beads in S1 comprises:
[0015] The glass beads are added to a sensitization solution and stirred at 100-150 rpm at 25-30°C for 5-15 min, wherein the sensitization solution contains 10 g / L stannous chloride dihydrate and 40 ml / L hydrochloric acid;
[0016] The glass beads are taken out and placed in an activation solution and stirred at 100-150 rpm at 25-30°C for 5-15 min, wherein the activation solution contains 1 g / L palladium dichloride and 30 ml / L hydrochloric acid.
[0017] The application further provides that the components of the plating solution comprise, by mass ratio:
[0018] Tetrabutyl titanate: 15%-20%;
[0019] Zirconium oxychloride: 5%-8%;
[0020] Polyethylene glycol 4000: 0.3%-0.8%;
[0021] Nitric acid: 2%-5%;
[0022] Cetyltrimethylammonium bromide: 0.05%-0.15%;
[0023] Diethanolamine: 0.5%;
[0024] The rest is deionized water.
[0025] The application further provides that the dynamic plating in S2 comprises:
[0026] After the glass beads are placed in the plating solution, they are pulled up at a speed of 1.5 mm / s while rotating at a speed of 30 rpm, and the process is repeated 3-5 times;
[0027] After plating, the glass beads are dried at 80°C for 25-30 min, then pre-sintered at 300°C for 1-1.5 h, and then crystallized at 500°C.
[0028] The application further provides that the 500°C crystallization process comprises:
[0029] Ramp to 350℃ at 5℃ / min, hold for 30min;
[0030] Ramp to 500℃ at 3℃ / min, hold for 2h.
[0031] The application further provides that the raw materials of the hydroxyl acrylic resin composite coating in S3 include, by weight ratio, 5-8 parts of perfluorooctyl triethoxysilane, 85-90 parts of hydroxyl acrylic resin composite coating, and 3-5 parts of nano-silicon dioxide.
[0032] The application further provides that the microwave curing treatment after the post-treatment in S3 is performed in the following manner:
[0033] The glass beads are cleaned with ethanol for 3-5min, and dried with hot air at 80℃ for 20-25min.
[0034] The glass beads are subjected to microwave curing treatment at a power of 500W and a microwave frequency of 2.45GHz for 2-3min.
[0035] The application provides a coating process method of high-refractive, wear-resistant glass beads.
[0036] The application uses waste glass as raw material to reduce the production cost, and improves the coating bonding strength of the glass beads through the activation treatment of the glass beads, and realizes in-situ plating of titanium dioxide on the surface of the glass beads by using tetrabutyl titanate, zirconium oxychloride, polyethylene glycol 4000, nitric acid, cetyltrimethylammonium bromide and diethanolamine, so that the glass beads have good wear resistance while the refractive index is improved, and the application of the glass beads in asphalt pavement is supported by high refractive index and high wear resistance. BRIEF DESCRIPTION OF DRAWINGS
[0037] Figure 1 The figure is a process flowchart of the application. DETAILED DESCRIPTION
[0038] The technical solutions in the embodiments of the application will be described clearly and completely below with reference to the drawings in the embodiments of the application.
[0039] Please refer to Figure 1 The embodiments of the application provide the following technical solutions:
[0040] Embodiment 1
[0041] A coating process method of high-refractive, wear-resistant glass beads, specifically comprising the following steps:
[0042] S1, cleaning and impurity removal of the glass beads, specifically including:
[0043] The waste glass is put into an electric melting furnace to be remelted to prepare glass microbeads with a size of 60-120 meshes;
[0044] The glass microbeads are soaked in 5wt% hydrofluoric acid and ultrasonically cleaned for 15 minutes;
[0045] The glass microbeads are fished out and sprayed with deionized water for 3 minutes;
[0046] The impurities are removed by using ethanol vapor to dry the glass microbeads for 10 minutes.
[0047] The glass microbeads are then subjected to surface activation treatment, and the specific treatment method includes:
[0048] The glass microbeads are added to a sensitization solution and stirred at 100 rpm at 25°C for 15 minutes, wherein the sensitization solution contains 10 g / L stannous chloride dihydrate and 40 ml / L hydrochloric acid. It should be noted that a tin strip is added to the sensitization solution during the process and the tin strip is always present.
[0049] The glass microbeads are fished out and placed in an activation solution and stirred at 100 rpm at 25°C for 15 minutes, wherein the activation solution contains 1 g / L palladium dichloride and 30 ml / L hydrochloric acid.
[0050] S2, the glass microbeads are soaked in a plating solution for dynamic plating to form a chemical bond Ti-O-Si on the surface of the glass microbeads, the plating layer thickness uniformity is ±5 nm, the refractive index gradient is controllable, and titanium dioxide is generated in situ during the plating process through hydrolysis-polycondensation reaction of tetrabutyl titanate, wherein the components of the plating solution include:
[0051] Tetrabutyl titanate: 15%;
[0052] Zirconium oxychloride: 5%;
[0053] Polyethylene glycol 4000: 0.3%;
[0054] Nitric acid: 2%;
[0055] Cetyltrimethylammonium bromide: 0.05%;
[0056] Diethanolamine: 0.5%;
[0057] The rest is deionized water.
[0058] Further, in order to ensure the plating effect, the dynamic plating method includes:
[0059] After the glass microbeads are placed in the plating solution, they are pulled up at a speed of 1.5 mm / s while rotating at a speed of 30 rpm, and the process is repeated 5 times;
[0060] After coating, dry at 80℃ for 25min, then pre-sinter at 300℃ for 1h, then perform 500℃ crystallization treatment, which includes:
[0061] Ramp up to 350℃ at 5℃ / min, hold for 30min;
[0062] Ramp up to 500℃ at 3℃ / min, hold for 2h.
[0063] It should be noted that the preparation method of the above coating solution specifically includes the following steps:
[0064] S21, add zirconium oxychloride to deionized water to prepare a 0.2mol / L mother liquor, add 0.5wt% hydrochloric acid to prevent hydrolysis, and stir magnetically at 40℃ until completely dissolved;
[0065] S22, mix the mother liquor with 0.1g / L cetyltrimethylammonium bromide, add polyethylene glycol 4000, stir at 300rpm in a 40℃ water bath for 30min, and obtain A liquid;
[0066] S23, mix the tetrabutyl titanate with diethanolamine, then ice-bath cool to 5℃, and add dropwise to the A liquid at a rate of 0.5mL / min while maintaining 500rpm stirring;
[0067] S24, adjust the pH of the system to 2.5 with 65wt% nitric acid, continue stirring for 1h, then transfer to a 25℃ constant temperature oven for aging for 24h, and obtain the coating solution.
[0068] S3, spray a composite coating of perfluorooctyltriethoxysilane and hydroxy acrylic resin on the glass beads, the raw materials of the composite coating including: perfluorooctyltriethoxysilane 5 parts: hydroxy acrylic resin composite coating 85 parts: nano silicon dioxide: 3 parts;
[0069] After natural drying, immerse in a 1wt% γ-aminopropyltriethoxysilane ethanol solution for 15min, wash the glass beads with ethanol for 5min, use 80℃ hot air drying for 25min, microwave curing treatment of the glass beads at a power of 500W and a microwave frequency of 2.45GHZ for 3min, and obtain high-refractive wear-resistant glass beads.
[0070] Example 2
[0071] The difference between this example and Example 1 is:
[0072] The surface of the glass beads is treated with a catalytic treatment, which includes:
[0073] Glass microspheres are added to the sensitization solution, stirred at 130 rpm for 10 min at 28℃, wherein the sensitization solution contains 10 g / L stannous chloride dihydrate and 40 ml / L hydrochloric acid;
[0074] Glass microspheres are fished out and placed in the activation solution, stirred at 130 rpm for 10 min at 28℃, wherein the activation solution contains 1 g / L palladium dichloride and 30 ml / L hydrochloric acid.
[0075] The components of the plating solution include, by mass ratio:
[0076] Tetrabutyl titanate: 18%;
[0077] Zirconium oxychloride: 7%;
[0078] Polyethylene glycol 4000: 0.5%;
[0079] Nitric acid: 4%;
[0080] Cetyltrimethylammonium bromide: 0.11%;
[0081] Diethanolamine: 0.5%;
[0082] The balance is deionized water.
[0083] The dynamic plating method includes:
[0084] After the glass microspheres are placed in the plating solution, they are pulled up at a speed of 1.5 mm / s while rotating at a speed of 30 rpm, and the process is repeated 4 times;
[0085] After plating, dry at 80℃ for 25 min, then pre-sinter at 300℃ for 1.2 h, and then perform 500℃ crystallization treatment, which includes:
[0086] Rise to 350℃ at a rate of 5℃ / min, and hold for 30 min;
[0087] Rise to 500℃ at a rate of 3℃ / min, and hold for 2 h.
[0088] The raw materials of the perfluorooctyl triethoxysilane and hydroxy acrylic resin composite coating include, by weight ratio: perfluorooctyl triethoxysilane 7 parts: hydroxy acrylic resin composite coating 88 parts: nano silicon dioxide: 4 parts;
[0089] After natural drying, immerse in a 1 wt% γ-aminopropyl triethoxysilane ethanol solution for 13 min, wash the glass microspheres with ethanol for 4 min, dry at 80℃ with hot air for 22 min, microwave solidification treatment of the glass microspheres at a power of 500W and a microwave frequency of 2.45GHZ for 2 min, and obtain high-refractive wear-resistant glass microspheres.
[0090] Example 3
[0091] The difference between this embodiment and embodiment 1 is that:
[0092] The glass microspheres are subjected to surface active catalytic treatment. The specific treatment methods include:
[0093] Add glass microbeads to a sensitizing solution containing 10 g / L stannous chloride dihydrate and 40 ml / L hydrochloric acid, and stir at 150 rpm for 5 min at 30°C.
[0094] The glass beads were fished out and placed in an activation solution containing 1 g / L palladium dichloride and 30 ml / L hydrochloric acid, and stirred at 150 rpm at 30° C. for 5 min.
[0095] The components of the coating solution include:
[0096] Tetrabutyl titanate: 20%;
[0097] Zirconium oxychloride: 8%;
[0098] Polyethylene glycol 4000: 0.8%;
[0099] Nitric acid: 5%;
[0100] Hexadecyltrimethylammonium bromide: 0.15%;
[0101] Diethanolamine: 0.5%;
[0102] The balance is deionized water.
[0103] Dynamic coating methods include:
[0104] After placing the glass beads in the coating solution, pull them up at a speed of 1.5 mm / s while rotating them at 30 rpm, repeating this three times.
[0105] After coating, the film is dried at 80°C for 30 minutes, pre-sintered at 300°C for 1.5 hours, and then crystallized at 500°C. The 500°C crystallization treatment includes:
[0106] Raise the temperature to 350°C at a rate of 5°C / min and keep warm for 30 min;
[0107] Raise the temperature to 500°C at a rate of 3°C / min and keep warm for 2h.
[0108] The raw materials of the composite coating of perfluorooctyl triethoxysilane and hydroxy acrylic resin include, by weight, 8 parts of perfluorooctyl triethoxysilane: 90 parts of the composite coating of hydroxy acrylic resin: 5 parts of nano silicon dioxide;
[0109] After natural drying, the glass beads are immersed in 1wt% gamma-aminopropyl triethoxysilane ethanol solution for 10 minutes, washed with ethanol for 3 minutes, dried with hot air at 80 DEG C for 20 minutes, treated with microwave curing at 500W power and 2.45GHz microwave frequency for 3 minutes, and high-refractive wear-resistant glass beads are obtained.
[0110] Further, the obtained high-refractive wear-resistant glass beads are classified, high-refractive wear-resistant glass beads less than 80 mesh are classified as A, high-refractive wear-resistant glass beads between 80 mesh and 100 mesh are classified as B, and high-refractive wear-resistant glass beads more than 100 mesh are classified as C, in use, the A, B and C are mixed in a ratio of 5:3:2, and the high-refractive wear-resistant glass beads are added to asphalt in a mass ratio of 1:10.
[0111] In the simulation experiment, the aluminized glass beads, pure TiO2 coated glass beads and zirconium coated glass beads are used as comparative examples, the advantages of the high-refractive wear-resistant glass beads in refractive index and wear resistance are explored, the refractive index is tested by Abbe refractometer according to ASTM D542 standard, and the wear resistance is tested by Taber abrasion tester according to ASTM D1044 standard, and the results are shown in Table 1.
[0112] Table 1
[0113] refractive index abrasion resistance (g / 1000r) alumina-coated microbeads 1.7-1.8 >0.3 Pure TiO2 coating 1.8-1.9 >0.2 zirconia-coated microbeads 1.6-1.7 0.1-0.2 the invention 1.9-2.0 <0.05
[0114] As shown in Table 1, the high-refractive wear-resistant glass beads provided by the application have obvious advantages in refractive index, and can be judged to have better light reflection suppression effect, and the high-refractive wear-resistant glass beads provided by the application have better wear resistance, which makes the high-refractive wear-resistant glass beads have a longer service life when applied to asphalt pavement.
[0115] Although the embodiments of the application have been shown and described, it can be understood by those skilled in the art that various changes, modifications, replacements and variations can be made to the embodiments without departing from the principles and spirits of the application, and the scope of the application is defined by the appended claims and their equivalents.
Claims
1. A coating process for high refractive index, wear-resistant glass microspheres, characterized in that: The specific steps include: S1. After cleaning and removing impurities from the glass beads, the glass beads are subjected to surface active catalytic treatment; S2, immersing the glass beads in the coating solution for dynamic coating; S3. Spray a composite coating of perfluorooctyl triethoxysilane and hydroxy acrylic resin on the glass microbeads, naturally dry them, immerse them in a 1 wt% γ-aminopropyl triethoxysilane ethanol solution for 10 to 15 minutes, perform post-treatment, and then perform microwave curing to obtain high-refractive wear-resistant glass microbeads.
2. The coating process of a high refractive index, wear-resistant glass microsphere according to claim 1, characterized in that: The method of cleaning and removing impurities from the glass beads in S1 includes: The waste glass is put into an electric melting furnace for remelting to prepare 60-120 mesh glass beads; The glass beads were immersed in 5 wt % hydrofluoric acid and ultrasonically cleaned for 15 min; Remove the glass beads and spray them with deionized water for 3 minutes; The mixture was dried with ethanol vapor for 10 min to complete the removal of impurities.
3. The coating process of a high refractive index, wear-resistant glass microsphere according to claim 1, characterized in that: The method of performing surface active catalytic treatment on the glass microspheres in S1 includes: Add glass microbeads to the sensitizing solution, and stir at 100-150 rpm for 5-15 minutes at 25-30°C. The sensitizing solution contains 10 g / L stannous chloride dihydrate and 40 ml / L hydrochloric acid. The glass beads are removed and placed in an activation solution, and stirred at 100-150 rpm for 5-15 minutes at 25-30° C., wherein the activation solution contains 1 g / L palladium dichloride and 30 ml / L hydrochloric acid.
4. The coating process of a high refractive index, wear-resistant glass microsphere according to claim 1, characterized in that: The components of the plating solution include, by mass ratio: Tetrabutyl titanate: 15% to 20%; Zirconium oxychloride: 5% to 8%; Polyethylene glycol 4000: 0.3% to 0.8%; Nitric acid: 2% ~ 5%; Hexadecyltrimethylammonium bromide: 0.05% to 0.15%; Diethanolamine: 0.5%; The balance is deionized water.
5. The coating process of high refractive index, wear-resistant glass microspheres according to claim 1, characterized in that: The dynamic coating method in S2 includes: After placing the glass beads in the coating solution, pull them up at a speed of 1.5 mm / s while rotating them at 30 rpm, repeating 3 to 5 times; After coating, it is dried at 80℃ for 25-30min, pre-sintered at 300℃ for 1-1.5h, and then crystallized at 500℃.
6. The coating process of high refractive index, wear-resistant glass microspheres according to claim 5, characterized in that: The 500°C crystallization treatment method includes: Raise the temperature to 350°C at a rate of 5°C / min and keep warm for 30 min; Raise the temperature to 500°C at a rate of 3°C / min and keep warm for 2h.
7. The coating process of high refractive index, wear-resistant glass microspheres according to claim 1, characterized in that: The raw materials of the perfluorooctyl triethoxysilane and hydroxy acrylic resin composite coating in S3 include, by weight, 5 to 8 parts of perfluorooctyl triethoxysilane: 85 to 90 parts of hydroxy acrylic resin composite coating: 3 to 5 parts of nano silicon dioxide.
8. The coating process of high refractive index, wear-resistant glass micro beads according to claim 1, characterized in that: The method of performing microwave curing after post-processing in S3 includes: Wash the glass beads with ethanol for 3-5 minutes and dry them with hot air at 80°C for 20-25 minutes; The glass microspheres were microwave cured for 2 to 3 minutes at a power of 500 W and a microwave frequency of 2.45 GHZ.
